THE INFLUENCE OF EXTERNAL FACTORS ON OBEDIENCE TO COLLECT THE REPORT OF MINIMUM SERVICE STANDARD AT SURABAYA HAJJ GENERAL HOSPITAL - Silvia Putri Sintia Dewi; Inka Kartika Ningsih; Thinni Nurul Rohmah (The Indonesian Journal of Public Health, 2022)
Introduction: Quality is the suitability between the work carried out and the standards or requirements that have been set. As a quality guideline, hospitals in Indonesia use minimum service standards. Based on the operational report of Surabaya Hajj General Hospital in 2016, it shows that 62.09% of units are non-obedient in collecting minimum service standard reports and 23.66% of units have collected minimum service standard-reports within a time set, that means in 12 months during 2016 from 31 working units only four units are obedient in collecting minimum service standard reports. Methods: The research population is 31 heads of work units of minimum service standard reports in each work unit at Surabaya Hajj General Hospital. Sample calculation uses a simple random sampling technique with confidence interval 0.05 so that a large sample is obtained, 29 unit heads. Result: The results of the obedience influence test in collecting a minimum service standard reports use a logistical regression of five variables to indicate if, between location status (p=0.154), legitimacy of an authority figure (p=0.661), authority figure status (p=0.782), and proximity of authority figure (p=0.711) have no significant effect. Meanwhile, peer support (p=0.009) has a significant influence on officer obedience in collecting minimal service standards reports. Conclusion: the support of colleagues from each subunit needs to be improved and also by providing training on interpersonal communication to officers to more easily communicate with colleagues, as well as holding discussion forums between officers in work units attended by management to improve relations between employees.